The role of algae in structuring reef communities: innovative monitoring and ecological insights within a Mediterranean conservation priority area - de Bettignies, Thibaut; Vanalderweireldt, Lucie; Launay, Marie; Moutardier, Grégoire; Pasqualini, Vanina; Durieux, Éric; Le Gall, Line (Frontiers in Marine Science, 2025)
The Mediterranean Sea is a “sea under siege”, facing numerous anthropogenic pressures leading to the spread of invasive species and the degradation of reefs, particularly the reduction of habitat-forming macroalgae to turf algae or sea urchin barrens. The coastal waters of Corsica, often considered as a “reference state” due to their lower human impact, have not been thoroughly studied with regard to infralittoral reef communities. This study aimed to characterize these communities and identify their biotic and abiotic drivers through an innovative monitoring protocol (VIT-Reef). From 2019 to 2021, we monitored infralittoral reef communities at 59 sites between 15 and 35 m depth within and adjacent to three MPAs, using innovative rapid assessment dive surveys for 74 benthic taxa. Our results highlighted vertical zonation in reef communities, in particular the depth extent of photophilic algae and the emergence of pre-coralligenous communities. Important ecological implications of taxa covariation were discussed, such as the negative relationship between canopy-forming macroalgae and the invasive algae, Caulerpa cylindracea. Notably, geographical contrasts were observed along northern, southern and western MPAs, primarily influenced by algal community changes. Cystoseira (sensu lato) forests were identified as the climax state on western reefs, while northern and southern reefs showed significant cover of Dictyota spp. and crustose corallines respectively, with concerning levels of Caulerpa cylindracea in deeper southern reefs. Our results underscored the structuring role of Cystoseira spp. forests and the effects of light, nutrients and Posidonia oceanica meadows extending into the reefs. This study highlighted the role of algae in structuring reef communities and will contribute to establish a baseline for conservation planning and predicting future changes in these high priority infralittoral communities.